Defining indocyanine green fluorescence to assess anastomotic perfusion during gastrointestinal surgery: systematic review. Issue 2 (24th April 2021) - Slooter, M D; Mansvelders, M S E; Bloemen, P R; Gisbertz, S S; Bemelman, W A; Tanis, P J; Hompes, R; van Berge Henegouwen, M I; de Bruin, D M
Abstract: Background: The aim of this systematic review was to identify all methods to quantify intraoperative fluorescence angiography (FA) of the gastrointestinal anastomosis, and to find potential thresholds to predict patient outcomes, including anastomotic leakage and necrosis. Methods: This systematic review adhered to the PRISMA guidelines. A PubMed and Embase literature search was performed. Articles were included when FA with indocyanine green was performed to assess gastrointestinal perfusion in human or animals, and the fluorescence signal was analysed using quantitative parameters. A parameter was defined as quantitative when a diagnostic numeral threshold for patient outcomes could potentially be produced. Results: Some 1317 articles were identified, of which 23 were included. Fourteen studies were done in patients and nine in animals. Eight studies applied FA during upper and 15 during lower gastrointestinal surgery. The quantitative parameters were divided into four categories: time to fluorescence (20 studies); contrast‐to‐background ratio (3); pixel intensity (2); and numeric classification score (2). The first category was subdivided into manually assessed time (7 studies) and software‐derived fluorescence–time curves (13). Cut‐off values were derived for manually assessed time (speed in gastric conduit wall) and derivatives of the fluorescence–time curves (Fmax, T1/2, TR and slope) to predict patient outcomes. Conclusion: Time to fluorescence seems the most promising category for quantitation of FA. Future research might focus on fluorescence–time curves, as many different parameters can be derived and the fluorescence intensity can be bypassed. However, consensus on study set‐up, calibration of fluorescence imaging systems, and validation of software programs is mandatory to allow future data comparison. Abstract : Antecedentes: El objetivo de esta revisión sistemática fue identificar todos los métodos para cuantificar una angiografía de fluorescencia ( fluorescence angiography, FA) intraoperatoria en anastomosis gastrointestinales y encontrar umbrales que pueden predecir los resultados en el paciente, incluida la fuga anastomótica y la necrosis. Métodos: Esta revisión sistemática se adhirió a las normas PRISMA ( Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines ). Se realizó una búsqueda bibliográfica en PubMed y Embase. Se incluyeron aquellos artículos en los que se realizó una FA con verde de indocianina para evaluar la perfusión gastrointestinal, en humanos o animales, y se analizó la señal de fluorescencia utilizando variables cuantitativas. Se definió una variable como "cuantitativa" cuando potencialmente se podía establecer un umbral numérico diagnostico respecto a los resultados del paciente. Resultados: Se identificaron 1.317 artículos, de los que se incluyeron 23. Catorce estudios se habían efectuado en seres humanos y 9 en animales. Ocho estudios realizaron la FA durante cirugías gastrointestinales altas y 15 durante cirugías gastrointestinales bajas. Las variables cuantitativas se dividieron en cuatro categorías: (1) tiempo hasta la fluorescencia ( n = 20), (2) relación con el contraste de fondo ( n = 3), (3) intensidad de píxeles ( n = 3) y (4) puntuación numérica clasificatoria ( n = 2). La primera categoría se subdividió en (1a) cuando el tiempo hasta la fluorescencia se evaluó manualmente ( n = 7) y (1b) cuando se realizaron curvas de tiempo de fluorescencia mediante programas informáticos ( n = 13). Los valores de corte para predecir los resultados en el paciente se obtuvieron para el tiempo evaluado manualmente (velocidad en la pared del conducto gástrico) y para el estimado mediante curvas de fluorescencia (Fmáx, T1 / 2, TR y pendiente). Conclusión: El tiempo hasta la fluorescencia parece ser la variable más prometedora para la cuantificación de la FA. La investigación futura debería centrarse en las curvas de tiempo hasta la fluorescencia, ya que de ellas se pueden derivar muchas variables diferentes y se puede evitar la intensidad de fluorescencia. Sin embargo, es obligado llegar a un consenso sobre la configuración del análisis, la calibración de los sistemas de imágenes de fluorescencia y la validación de los programas informáticos para permitir, en el futuro, la comparación de datos. The purpose of this systematic review was to provide an overview of all methods used to quantify fluorescence angiography of the gastrointestinal anastomosis, and to identify a threshold that could predict patient outcomes, including anastomotic leakage and necrosis. Four categories of quantitative parameter were identified: time to fluorescence; contrast‐to‐background ratio; pixel intensity; and numeric classification score. Cut‐off values were derived only for the first category; thus, time to fluorescence seems the most promising method for quantitation of fluorescence angiography. Time for standardisation